THE DISCOURSE OF ETHICS AND ITS INFLUENCE ON THE DYNAMICS OF TEACHING AND TUTORIAL ACTION - Callalli Pimentel, Aldo (2014)
The leitmotiv of this article is testing ideas about the discourse of ethics and the importance of their impact both on the dynamics of teaching-learning process in the exercise of the tutorial, in order to realize an adequate education educational content that involves not only conceptual and practical skills but also values for integration and promotion, from the classroom space, the human in society under the legal norms of democratic rule of law.